Impact of complete vaccination againts COVID-19 on lethality and deaths per million habitants in America 06/05/2022 - Mora-Alvarado, Darner A. (2023)
This study addresses the impact of complete vaccination with two doses against COVID-19, on the case fatality rates and deaths million habitants, of the disease in 33 countries in America up to 06/05/2022. To meet this objective, the data were collected on confirmed cases, deaths, lethality, deaths/million habitants and vaccination against the COVID-19, among others from the digital platforms “datosmacro.expansion.com” and “Statista.com”. The impact of complete vaccination was assessed by applying the partial correlations between the percentages of coverage of vaccination versus lethality rates and deaths/million inhabitants. The results of America differ greatly from the other four continents and globally, because the “r” values of vaccination with both variables indicate positive associations (>1). Contrary to what is observed in the other continents, specifically between vaccination and lethality, where the association was inverse (-1 to 0.0), due to the greater coverage of progress in complete vaccination, the lower the mortality from COVID-19. However, in the case of the COVID-19 deaths/million population indicador, the assessment of the impact of vaccination is not as sensitive as in the case of fatality rates, defined as COVID-19 deaths/confirmed cases for the disease up to 06/05/2022.